Determinan Produktivitas Tenaga Kerja Industri Manufaktur Besar dan Sedang di Pulau Jawa - Sari, Rika Dwi Puspita; Oktora, Siskarossa Ika (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
Industrialization is one of the government’s focuses on development. Java is an area focused on the industry. However, the labor productivity of large and medium manufacturing industries in Java is lower than regions outside Java and national level of productivity. This study aims to analyze determinants of labor productivity in large and medium manufacturing industries in all provinces in Java from 2010 to 2015 using panel data regression. As the best model, fixed effect model showed that HDI, real wages, and vehicle PMTB has a positively significant effect on labor productivity.